2018
DOI: 10.5152/tud.2018.98372
|View full text |Cite
|
Sign up to set email alerts
|

Delayed diagnosis of primary vesicoureteral reflux in children with recurrent urinary tract infections: Diagnostic approach and renal outcomes

Abstract: Objective: In this study, we aimed to assess renal outcomes of delayed diagnosis of dilating primary vesicoureteral reflux (VUR) following recurrent febrile urinary tract infections (fUTIs) and its diagnostic imaging procedures. Material and methods:The medical records of patients who underwent ultrasonography (US), non-acute dimercaptosuccinic acid (Tc-99mDMSA) scintigraphy and voiding cystourethrography (VCUG), and who were older than 2 years at the time of VUR diagnosis were retrospectively reviewed.Results… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(2 citation statements)
references
References 24 publications
0
2
0
Order By: Relevance
“…Thus, other diagnostic methods in combination with ultrasound should be used to monitor AP in pediatric patients due to the disadvantages such as the accepted low sensitivity, high operator dependence, and required expertise for the data interpretation [ 47 , 48 ]. It has been recently reported that the combined use of ultrasound with DMSA scintigraphy [ 49 ], voiding cystourethrogram [ 50 ], and technetium-99 m DMSA ( 99m Tc-DMSA) scintigraphy [ 51 , 52 ] can highly improve the diagnostic accuracy of AP among pediatric patients.…”
Section: Discussionmentioning
confidence: 99%
“…Thus, other diagnostic methods in combination with ultrasound should be used to monitor AP in pediatric patients due to the disadvantages such as the accepted low sensitivity, high operator dependence, and required expertise for the data interpretation [ 47 , 48 ]. It has been recently reported that the combined use of ultrasound with DMSA scintigraphy [ 49 ], voiding cystourethrogram [ 50 ], and technetium-99 m DMSA ( 99m Tc-DMSA) scintigraphy [ 51 , 52 ] can highly improve the diagnostic accuracy of AP among pediatric patients.…”
Section: Discussionmentioning
confidence: 99%
“…VUR in children could generate varying degrees of renal damage such as renal scarring, poor kidney growth, renal dysplasia, proteinuria, hypertension and impaired renal function. Therefore, besides ultrasonography and dimercaptosuccinic acid scintigraphy, we recommended that voiding cystourethrography be performed routinely in children with recurrent UTI . Nordenstrom et al .…”
Section: Discussionmentioning
confidence: 99%